Preparation and Drug Release Study of Novel Nanopharmaceuticals with Polysorbate 80 Surface Adsorption. (20th May 2018) - Tao, Xiaojun; Li, Yu; Hu, Qian; Zhu, Li; Huang, Zixuan; Yi, Jiajin; Yang, Xiaoping; Hu, Jianzhuo; Feng, Xing
Abstract : Most free drugs that cross the blood–brain barrier are characterized by high liposolubility, but they often have limited clinical applications because of poor dissolution and poor bioavailability. In this study, we prepared donepezil drug-loaded nanoparticles (DZP) with cholesterol-modified pullulan (CHP) as the nanocarrier (DZP-CHP) and surface modified the drug-loaded nanoparticles to improve the water solubility of donepezil while enhancing its targeting and sustained release. We determined the drug loading and encapsulation efficiency of DZP-CHP nanoparticles at different feed ratios. The mean ± SD drug loading and entrapment efficiency were high: 13.52 ± 2.03 and 86.54 ± 1.31. On dynamic light-scattering measurement, mean ± SD particle size was 260.7 ± 1.76 nm, polydispersity index 0.123 ± 0.004, and zeta potential −5.75 ± 0.64 mV. DZP-CHP nanoparticles prepared with the optimal feed ratio (DZP : CHP = 1 : 5) were coated with polysorbate 80, and the adsorption process was determined by isothermal titration calorimetry. We found good affinity between polysorbate 80 and DZP-CHP, with mean ± SD coverage 2.7 ± 0.372. The mean ± SD drug loading and entrapment efficiency of polysorbate 80-emulsified DZP-CHP nanoparticles were 8.25 ± 1.80 and 91.28 ± 4.57, respectively, and the proportion of drug released by 72 h was 42.71%. Compared to DZP-CHP alone, PS-DZP-CHP can enhance the release of donepezil.